Renal impairment at presentation is not an adverse prognostic factor in multiple myeloma patients treated with new agents - Neves,Manuel (2014)
Fifteen to forty per cent of multiple myeloma patients have renal impairment at diagnosis. The Durie-Salmon staging included renal impairment as an adverse prognostic factor and so does the International Staging System, since β2-microglobulin correlates with both tumour burden and renal impairment. However, the introduction of new therapeutic agents (as bortezomib, lenalidomide, and thalidomide) and new prognostic factors, such as cytogenetics, changed that view. With this paper, we intended to study the prognostic impact of renal insufficiency at presentation in patients with multiple myeloma treated with new agents. We retrospectively analysed, from July 2004 to December 2012, multiple myeloma patients treated in first line with bortezomib or thalidomide, in whom cytogenetic study was performed. Renal insufficiency was defined as creatinine clearance < 30mL/min, using the Cockcroft-Gault equation. We treated 174 patients, 54 with thalidomide (31%), 120 with bortezomib (69%). Eighty-eight patients were submitted to autologous stem-cell transplantation. Male sex = 50%, median age = 66 years (22-83). There were 13.4% of light chain myelomas. Creatinine clearance < 30mL/min in 20.1% of patients. International Staging System: I = 39.1%; II = 28.7% and III = 32.2%. High-risk cytogenetics = 35.1%. Median follow-up = 30 months, median overall survival = 83 months. In univariate analysis, the median overall survival was higher for patients without renal impairment compared to patients with renal impairment (83 vs. 40 months, p = 0.004). However, in multivariate analysis with the International Staging System and high-risk cytogenetics, renal impairment does not affect the overall survival. We concluded that renal impairment at presentation is not a prognostic factor in multiple myeloma patients treated in first line with new therapeutic agents.